Supply Chain Management Practices and Operational Performance: The Mediating Role of Process Control and Improvement - Roespinoedji, Roeshartono; lisdayanti, Annisa; Farida, Sasmi; Isa, Azizan Mohamed (International Journal of Supply Chain Management, 2019)
The reason for this study is to inspect the impact of TM, SM on OP alongside the mediating job of process control and enhancement. This is a quantitative report and was directed on Indonesian oil part. 300 survey were conveyed. Arbitrary inspecting method and 5 Likert scale was utilized to gather the data. The findings of this investigation demonstrated that SCM practices has a huge constructive outcome on the OP of SCM, this is an amazing methodology on the grounds that not just the SCM practices proposed in this examination, OP is additionally affected by others, for example, working environment, capital, innovation, hardware, human asset, data, and so on.